Inclusão dos catadores de matriais recicláveis e reutilizáveis: análise do Plano Municipal de Gestão Integrada de Resíduos Sólidos de João Pessoa - LOPES, Luana Ferreira (2015)
This study aims to understand and analyze the National Policy on Solid Waste (PNRS) established by the Brazilian Federal Law No. 12,305 / 10, next to the Municipal Plan of Integrated Solid Waste Management (PMGIRS) of the city of Joao Pessoa, in order to ensure the integration of reusable and recyclable material collectors in public policies developed in the city, given the determinations present in the law, sharing the same responsibility as the collected materials. In this way, the work was developed from an exploratory study, through literature and documentary. Given the questions about the management of solid waste and the inclusion of collectors as main actors of this cycle, the National Policy on Solid Waste, emphasizes the municipality's responsibility to create inclusion means for collectors of recyclable and reusable materials. The Municipality of João Pessoa drafted in August 2014 PMGIRS, which should enable access to the Union's resources, to apply to services related to urban cleaning and solid waste management, aimed at mitigating the environmental problems of the city. To provide resources for the management of solid waste, the collectors become main actors, analyzing the work of the same as extremely important to the advancement and improvement of solid waste management, which will bring benefits not only for collectors, as for the local economy and quality of life for all pessoense population.